2005
DOI: 10.1111/j.1365-2036.2005.02515.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the use of H. pylori tests in UK general practice – a qualitative study

Abstract: SUMMARYBackground: Although serology is the main Helicobacter pylori test used by general practitioners in the UK, there is no information available on variation in requesting rates. Aim: To explore the reasons for any variation in H. pylori serology testing by general practices in the UK using qualitative methods. Methods: Serology requesting rates were determined using laboratory and population data. Staff from randomly selected practices in the lowest and highest quintiles of testing attended focus groups t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Few GPs use or know about stool antigen tests or UBTs and there is concern amongst primary care clinicians in the UK that the stool test will not be culturally acceptable to patients. 7,8 GPs have suggested that patients and practices would accept stool testing if appropriately counselled about the improved accuracy over blood serology, and the ease of implementation in the practice setting. 9 There have not been any UK studies examining the acceptability of helicobacter stool tests.…”
Section: Introductionmentioning
confidence: 99%
“…Few GPs use or know about stool antigen tests or UBTs and there is concern amongst primary care clinicians in the UK that the stool test will not be culturally acceptable to patients. 7,8 GPs have suggested that patients and practices would accept stool testing if appropriately counselled about the improved accuracy over blood serology, and the ease of implementation in the practice setting. 9 There have not been any UK studies examining the acceptability of helicobacter stool tests.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important distinction given the well-documented lack of awareness among most general practitioners of the limitations of available tests for this organism. 2 More importantly, the authors do not state the proportion of their patients whose primary H. pylori infection was diagnosed serologically, a method with an inadequate positive predictive value (with high false-positive rates) when employed using commercially available kits in low prevalence populations such as that of England. [3][4][5][6] If, as the authors' other recent study suggests, 7 the majority of the patients included in the present study had their primary H. pylori infection diagnosed serologically by their general practitioner, one can only conclude that their estimate of the recurrence rate of this infection is flawed.…”
mentioning
confidence: 99%